El articulus en los gramáticos latinos (Minerva, 2019)
The Latin grammarians of Late Antiquity denied that the article belonged to a separate class of Latin words. They recognized, however, that one of the syntactical functions of the pronomen was denominated articulare pronomen or articulus (e.g. hic magister, hic sacerdos, haec sacerdos). A pointed discussion arose among grammarians regarding the syntactical function of the articulus when it preceded indefinite pronouns such as alter, alius; in these cases, some held, the pronouns turned into nouns, inasmuch as they ceased to be indefinite upon being preceded by a definite article (e.g. hic alter, hic alius). Priscian supplies light to appreciate the importance of the discrepancies among grammarians in their debate over the syntactical functions of Latin pronouns.